COMPARISON OF MSME FOOD TRADE SECTOR VIEWED FROM VARIOUS ASPECTS - Cintia Arruum; Raisha Jihad Denia Pinasty; Dwiani Nursasi Aprilia; Aisyah Putri Rizkia; Ira Rachmawati (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2023)
MSMEs are community economic activities that are small but have a big impact on the economy and can reduce unemployment in Indonesia. According to Law no. 20 of 2008 concerning MSMEs. After the Covid-19 pandemic, MSMEs began to rise slowly with the addition of MSMEs, but it is this competition that makes MSME have to adapt market developments with a digital ecosystem which has an impact on MSME income. One of the obstacles faced by SMEs to compete is from the aspect of marketing and preparation of financial reports. This study aims to compare the food trade business sector in terms of various aspects by conducting interviews with MSME actors in Cirebon City, Banyumas Regency, and Tegal Regency. Interviews were conducted offline by visiting MSME production houses. The results of this study are in the form of a comparison of management aspects, financial aspects, accounting aspects and taxation aspects of MSMEs. As much as more than 50% of MSMEs are hampered because their products are unable to compete and lack of capital, and financial reports prepared do not follow Financial Accounting Standards.